10T SRAM Using Half- V} Precharge and Row-Wise Dynamically Powered Read Port for Low Switching Power and Ultralow RBL Leakage - Maroof, Naeem; Bai-Sun Kong (IEEE transactions on very large scale integration (VLSI) systems, 2017)
We present, in this paper, a new 10T static random access memory cell having single ended decoupled read-bitline (RBL) with a 4T read port for low power operation and leakage reduction. The RBL is precharged at half the cell's supply voltage, and is allowed to charge and discharge according to the stored data bit. An inverter, driven by the complementary data node (QB), connects the RBL to the virtual power rails through a transmission gate during the read operation. RBL increases toward the V DD level for a read-1, and discharges toward the ground level for a read-0. Virtual power rails have the same value of the RBL precharging level during the write and the hold mode, and are connected to true supply levels only during the read operation. Dynamic control of virtual rails substantially reduces the RBL leakage. The proposed 10T cell in a commercial 65 nm technology is 2.47× the size of 6T with β = 2, provides 2.3× read static noise margin, and reduces the read power dissipation by 50% than that of 6T. The value of RBL leakage is reduced by more than 3 orders of magnitude and (I ON/ I OFF) is greatly improved compared with the 6T BL leakage. The overall leakage characteristics of 6T and 10T are similar, and competitive performance is achieved.